2013
DOI: 10.1111/jonm.12156
|View full text |Cite
|
Sign up to set email alerts
|

Nursing work: challenges for health management in the Northeast of Brazil

Abstract: Aim: Social exchange theory is used as the framework to examine the interaction between supervisor-subordinate relationships, training and affective commitment for Northeast Brazilian public sector nursing professionals.Background: There are continuing challenges to nursing management worldwide in terms of the supply of nursing professionals, their work relationships, nurse training and commitment to their employing organisations. The interplay between these factors for nurses in the Northeast of Brazil has no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…We observed that nurses with more than one job were more likely to suffer from personal bullying. A study from Brazil indicated that, because of low wages, nurses might need to work two or more jobs, making this population especially overloaded, and these working conditions affected their availability to participate in professional training and limited their relationship with supervisors (Nelson et al., 2013), which can make this population vulnerable to bullying. (Maringá, 2017), have enacted laws to deter and punish such practices in the public sector, but unfortunately there is still no such law at the state level.…”
Section: Discussionmentioning
confidence: 99%
“…We observed that nurses with more than one job were more likely to suffer from personal bullying. A study from Brazil indicated that, because of low wages, nurses might need to work two or more jobs, making this population especially overloaded, and these working conditions affected their availability to participate in professional training and limited their relationship with supervisors (Nelson et al., 2013), which can make this population vulnerable to bullying. (Maringá, 2017), have enacted laws to deter and punish such practices in the public sector, but unfortunately there is still no such law at the state level.…”
Section: Discussionmentioning
confidence: 99%
“…The managerial environment (for example poor interpersonal and people management skills) has been associated with workplace bullying (Dick, 2008). In relation to Brazil, the majority of research on work relationships among nursing professionals is qualitative in nature (Dalmolin et al, 2009) and it has become clear that follow-through quantitative or mixed methods research is also required (Nelson et al, 2013). It is not clear whether or not effective LMX is likely to minimize bullying and improve wellbeing in the northeast of Brazil, given the particular circumstances shaping nursing management in that region.…”
Section: Theoretical Backgroundmentioning
confidence: 97%
“…Allied to this, most hospitals in the country are driven by capitalism assumptions and the culture of classical administration (6) , therefore, they are not predisposed for the solidifi cation of a professional profi le able to articulate the managerial and care dimensions. This panorama can contribute so that nurses are primarily devoted to management demands (7) . In this sense, the dichotomy care/management has prevailed in the nurses discourse (3,8) , considering that they have the perception that there is no articulation between the two dimensions, they consider that managerial activities will lead to patient distance, which may result in confl icts with the rest of the nursing staff (9)(10) .…”
Section: Introductionmentioning
confidence: 99%